The relations between the multipole moments in axistationary electrovacuum spacetimes and the N-soliton solution - Costa Filho, Etevaldo dos Santos; Cabrera Munguia, Roberto Ivan; Costa Filho, Etevaldo dos Santos; guimarães, Angelo (2022)
A general formulation of the relativistic multipole moments in axistationary electrovac spacetimes is introduced in a closed analytical form. We give a complete description of how the Ernst potentials on the symmetry axis can be completely characterized by these arbitrary multipole moments. Some concrete applications are also developed.